Politics in the developing world - Burnell, Peter J.; Randall, Vicky (Oxford University Press, 2014)
The fourth, thoroughly updated, edition of this well-respected textbook explores the changing nature of politics in the developing world. Leading experts in the field consider theoretical approaches, society-state relations, and policies, with a series of illustrative country-based case studies